What Is The Thematic Interpretation of The Hypocritical Character In Qs. Al-Munafiqun? - Muhammad Nurul Huda; Eky Adhistia Rahmadianty; Andri Nirwana AN (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Al-Qur'an becomes the guide book of all human behavior and becomes the news that will definitely happen in the future. Al-Qur'an always warns mankind about everything, especially warns Muslims to be careful about various things. One of the warnings displayed in the Qur'an is the cunning of hypocrites. Al-Munafiqun is a letter that discusses the characters of hypocrites (munafiqun). The interpreters have interpreted surat al-Munafiqun well, but there are still many differences of opinion that can confuse laymen who are studying surat al-Munafiqun. That is why the writer will review and present the thematic interpretation of surat al-Munafiqun so that it can be understood by the general public. In order to compare and display the interpretation of surat al-Munafiqun in detail and in a structured manner, the writer uses a literature research method with a psychological approach. Data was collected from interpretation books, books of asbabun nuzul, and related articles. The discussion about the characters of hypocrites has several main points, there are: 1) Lie or mendacity; 2) Turning away from the truth; 3) break promises; And 4) Miserly.